The Sino-Indian rivalry in South Asia in the XXI century on the examples of Nepal, Sri Lanka and Maldives - Okraska, Tomasz (Political Preferences, 2018)
In the article the author focuses on the analysis of Sino-Indian rivalry in the three countries, seeking common points and differences in their situation. These are the inland Nepal, located between India and China; the islands of Sri Lanka, lying adjacent to the Indian subcontinent; and the Maldives, five hundred kilometer away from it. Author claims that in the 21st century there is an increase of intensity in relations between the People's Republic of China and the Republic of India in the field of competitive impacts in the analyzed countries. However, due to the significantly lower potential of India in the economic sphere and less activity in the international arena, the policy of this country in South Asia is most often reactive to China's actions. In the 21st century a significant change in the political situation in Nepal, Sri Lanka and the Maldives can be seen. India's former hegemony has been undermined by China, which has gained an advantage in all of these countries. Key words: India, China, South Asia, rivalry, sphere of influence